Tunisie, Le Khalifa de Djerba et la famille du caïd Ahmed b[e]n Bichem - Blanc, Édouard; Molteni (1889)
Keywords: Caïdat -- Djerba

Le Caïd et les autorités administratives de Djerba - Blanc, E.; Vivarès, L. (1888)
M. Hartmayer (vice-consul de France)
Keywords: Contrôleurs civils -- Tunisie

Full-length seated portrait of Saiyid Majid, Sultan of Zanzibar - Chintamon, Hurrichund (1867)
Studio portrait of Saiyid Majid, Sultan of Zanzibar, seated beside a table with his arm resting on a large book, by Hurrichund Chintamon in the 1860s. This photograph is from the Archaeological Survey of India Collections and was shown at the 1867 Paris Exhibition. Sultan Sayyid Majid was born at Zanzibar in 1834, the sixth son of His Highness Sayyid Said bin Sultan, Iman of Muscat and Oman. Sayyid Majid was Governor of Zanzibar, Pemba and the East African domains during his father's reign. On the death of his father, 19 October 1856 he was proclaimed Sultan of Zanzibar and Oman. He died at Zanzibar 7 October 1870. 21.5 x 18 Centimetres. Photographer: Chintamon, Hurrichund.
Keywords: Zanzibar

Full-length seated portrait of the Imam of Muscat - Chintamon, Hurrichund (1867)
A studio portrait of the Imam of Muscat (Oman) taken by Hurrichund Chintamon in the 1860s. This photograph is from the Archaeological Survey of India Collections and was shown at the 1867 Paris exhibition. It is unclear whether it was taken in Mumbai or Muscat (Masqat). Hurrichund Chintamon began one of the first photographic firms in Mumbai. 22.8 x 17.7 Centimetres. Photographer: Chintamon, Hurrichund.
Keywords: Biographies -- Oman -- 19e siècle

Phot. de la mosquée de Sidi Noh à Ngouça, entre Laghouat et Ghardaïa, Sahara algérien - Kalb, V. (1883)
Keywords: Sidi Nuh, mosquée (Ngouça, Ghardaïa)

2 phot. en double exemplaire des fouilles de Sedrata, au sud d'Ouargla, en 1881, phot. par Harold Tarry, donateur en 1886 - Tarry, Harold (1881)
Fouilles de Sedrata (au sud de Ouargla) : plans d'une maison et mur intérieur d'une maison. Fouilles de Sedrata (au sud de Ouargla) : mur intérieur d'une maison.
Keywords: Archéologie -- Sedrata